PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE CO-OP-CO-OP UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS - Delfian, Delfian (STKIP PGRI Sumatera Barat, 2014)
The main purpose of this research is to overcome the problems in the learning of Public Junior High School 1 Lubuk Basung. This research also aims to describe the improvement of student’s learning outcomes through the use of Cooperative Learning Model Type Co-Op-Co-Op in the learning of Social Studies Subject at the grade IX.4. The results show that the use of Cooperative Learning Model Type Co-Op-Co-Op can improve the student learning outcomes. It can be seen from the student’s average grade in the second cycle in which it is higher than the outcomes of the first cycle of learning increasing from 6.4 to 8.1. Thus, the use of Cooperative Learning Model Type Co-Op-Co-Op can improve the student’s learning outcomes in the learning of Social Studies Subject at the grade IX.4